Daddy Love [compact disc, unabridged] - Oates, Joyce Carol, 1938- (HighBridge Audio, 2013)
Dinah Whitcomb seemingly has everything. A loving and successful husband, and a smart, precocious young son named Robbie. Then one day, their worlds are shattered when Dinah is attacked and Robbie is abducted from a mall parking lot.